Process queuing in the automobile manufacturing body shop: Using a multi-objective model - Ali, A. J. Adham; Razman, Mat Tahar (Academic Journals, 2011)
The automobile industry is one of the most important industries in global economics. The automobile manufacturing industry consists of many shops and many stations. Each station has a number of operations, which depend on the number of welded pieces in those stations. One of these shops is the body shop. The problems that occur in the body shop concern queuing and the lead time between stations. This paper focus on optimize queuing processes and lead time in the body shop at the production line. A multi-objective model was applied to create a balance of equal finishing of all operations in all stations at the same time and to reduce the lead time in transferring the car structure between stations. The result showed that saving time and ensuring maximum production can increase profits in the automobile manufacturing industry.